New model for Export Led Growth / Maizatul Saadiah Mohamad, Maymunah Ismail and Abdul Rahim Ridzuan - Mohamad, Maizatul Saadiah; Ismail, Maymunah; Ridzuan, Abdul Rahim (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This New model was build base on the result from our research paper "re-investigates the evidence of Export-Led-Growth evidence in Malaysia: bound test approach". The data used in this paper is annually data range from 1980 to 2011. By modifying the standard Cobb-Douglas production function, we found that export play significant role in contributing growth to the Malaysia's economy. Besides, labor and capital are also importance for the development of the nation. From This result of paper we build one model by applying the production of Cobb Douglas function and combine with the aggregate supply curve to produce our innovation model. Based on standard Cobb Douglas production function which consist of labor (L) and capital (CP), we introduce new variables such as export (X), import (M), and exchange rate (EXR) as one of the determining variables for output growth (GDP) for Malaysia. Moreover, we also found that the hypothesis of export led growth in the Malaysian economy is supported in both short run and long run. Figure 1 show the diagram that determines the relation between GDP with labor, capital, exchange rate, export and import. This idea can be commercialized by government in their policy for our country. As for policy recommendation, since export (X) seem to be one of the major determinant for Malaysian economy, the government should implement effective macroeconomic policies in stabilizing its trade balance, liberalizing the country's trade and attracting export-oriented foreign direct investment into the country. Besides, the government should ensure there is enough supply of labor and capital in the market given that it would lead to a higher level of economic growth.